Subdiaphragmatic extranodal localizations at diagnosis of primary mediastinal large B-cell lymphoma: an impressive, rare presentation with no independent effect on prognosis. (August 2021) - Karakatsanis, Stamatis; ,; Papageorgiou, Sotirios G.; Michail, Michail; Angelopoulou, Maria K.; Kalpadakis, Christina; Leonidopoulou, Theoni; Katodritou, Eirini; Kotsopoulou, Maria; Kotsianidis, Ioannis; Hatzimichael, Eleftheria; Lakiotaki, Eleftheria; et al.
Highlights: PMLBCL rarely extends to extranodal subdiaphragmatic (ES) sites at diagnosis. Among 455 patients, 32 (7%) had such localization at baseline. Kidney, liver, and adrenals were most frequently involved. ES site involvement had not independent prognostic impact beyond that of stage IV.